Sorne family and school characteristics affecting the etiology or emotional disturbance - Jadue, Gladys (2000)
This paper analyses and describes sorne importan! characteristics of families and the school affecting the students both in their psychosocial development and their school performance. It also emphasizes the characteristics of anxiety that can be trigger by the school and that together with sorne family anxiety peculiarities can increase the number of children who are at risk of having a low school performance and school failure. This paper suggest that in order to improve student's psychosocial development together with school performance, it is important to have an efficient intersystemic communication between the family and the school. It is also importan! to apply reliable strategies, as those contained in the Chilean Educational Reform so as to achieve these goals.